PENGARUH KOMPETENSI TERHADAP KINERJA GURU DIMODERASI OLEH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI - Budi Prasetyo, 11.52.02.0047 (Students Journal of Economic and Management, 2013)
This study aims to reveal the influence of (i) Competency on the Teacher Performance, (ii) the Principal Leadership on Teacher Performance, (iii) Organizational Climate on the Performance of Teachers, (iv) Test the Effect Competence on Performance Teacher and Principal Leadership moderated, (v ) Testing the Effect Competency on Teacher Performance moderated School Organizational Climate in junior High School Teachers in UPT Jakenan and UPT Pucakwangi District Pati. The research is Field Reseach, using a quantitative approach. The population in this study were all teachers at the Junior High School in UPT Jakenan and UPT Pucakwangi District Pati, 112 Responden., collect data by census method. Test instruments using the Test Validity, Reliability and OLS. Analysis using linear regression analysis model testing, R2 Test, F Test, hypothesis testing using the t test. The results of (i) Competence positive and significant impact on teacher performance is 0,031, (ii) the principals leadership and significant positive effect on teacher performanceis is 0,024, (iii) no significant Organizational Climate on the Performance of Teachers is 0,124, (iv) Principal Leadership Not Moderating influence of Competency on the Teacher Performance is 0,259, (v) Organizational Climate as Moderating Effect Competency.on Teacher Performance is 0,75. Â Keywords: Competence; Leadership Principal; Organizational Climate and Teacher Performance.